The Impact of Covid-19 Outbreak on Banking Policies in Indonesia (Jurnal Scientia Indonesia, 2022)
This research is descriptive analysis and uses a statutory approach. This research also uses qualitative juridical analysis which is conducted by using inductive deductive thinking method and vice versa. Conducted to find out and describe the corona virus impact on regulation in banking sector, and how the Financial Services Authority’s role for protecting banking consumers affected by Covid-19. The impact of Covid-19 has an economic activities impact, including in banking sector, which causes debtors to experience difficulties in carrying out achievements. Although, the government issued several policies including the existence of regulations regarding State Financial Policy and Financial System Stability for Handling the Corona Virus Disease 2019 Pandemic or in the Context of Facing Threats that Endanger the National Economy and Financial System Stability. Furthermore, the Financial Services Authority as a banking supervisory institution also took part in and supported the Government's policies, namely by issuing several policies in order to protect customers affected by Covid-19, through its policies, banking institutions are required to implement a credit relaxation program like credit restructuring for affected customers.